The influence of physical factors on the viability of the seed material Echinacea purpureavariety “Livadia” - Gavrilkova Е.А.; Tleukenova, S.U.; Mussina, R.T.; Kali А.К. (Fundamental and Experimental Biology, 2022)
This article presents data on the germination of Echinacea purpurea seeds of the variety “Livadia” as a result of the influence of physical factors. The seed material was previously cryogenically stored for a day, then the seeds were exposed to laser irradiation and magnetic fields for a certain time, and the bubbling method was also used in the experiment. As a result of the conducted studies, it was found that seeds exposed to magnetic fields retain their viability, but there is no improvement in germination indicators compared to the control group. Positive dynamics in seed germination and the passage of ontogenesis phases were observed in experimental variants with preliminary cryogenic storage of seeds and subsequent bubbling for one day, germination rates were comparable with control values. The seed material irradiated with a He-Ne laser beam showed a decrease in germination rates compared to the control group.